Hi!
I have two functions that I've determined are even, odd or neither. Now I need to solve them algebraically, but it's been a few months since I've factored (I'm in a college algebra 111 class) (took a term off to fufill other class requirements) and in that time I have forgotten more than I though was posssible!! Ugg. Below are the functions.
f(x) = x^3 - 2x
TEST: f(-x) = (-x)^3 -2(-x)
=-x^3 + 2x
Signs change, ODD
However, how do I factor this? I see the GCF of x, which gives me is x(x^2 - 2) but what do I do after that? Please show me step by step.
Then, there's f(x) = 3x - x^2
TEST: f(-x) = 3(-x) - (-x)^2
=-3x - x^2
Signs different, neither.
Factoring f(x) =3x - x^2
GCF
x(3-x)
After that?
I have two functions that I've determined are even, odd or neither. Now I need to solve them algebraically, but it's been a few months since I've factored (I'm in a college algebra 111 class) (took a term off to fufill other class requirements) and in that time I have forgotten more than I though was posssible!! Ugg. Below are the functions.
f(x) = x^3 - 2x
TEST: f(-x) = (-x)^3 -2(-x)
=-x^3 + 2x
Signs change, ODD
However, how do I factor this? I see the GCF of x, which gives me is x(x^2 - 2) but what do I do after that? Please show me step by step.
Then, there's f(x) = 3x - x^2
TEST: f(-x) = 3(-x) - (-x)^2
=-3x - x^2
Signs different, neither.
Factoring f(x) =3x - x^2
GCF
x(3-x)
After that?
Last edited: